An uncommon case of intraperitoneal urinary bladder rupture in an adult with pelvic bone fracture - Gupta, Rekha; J., Vivek (International Surgery Journal, 2018)
Injury of urinary bladder can occur due to blunt, penetrating, or iatrogenic trauma. Here, author present an uncommon case of Intraperitoneal bladder rupture in an adult patient with associated pelvic bone fracture. Following a fall from his house, a 40 years old male patient presented with haematuria and abdominal pain. CT scan of abdomen revealed Intraperitoneal bladder rupture with pelvic bone fracture. Intraoperative findings revealed intraperitoneal rupture of bladder with a defect in dome region. It was repaired with Vicryl 2-0 suture. So, a high degree of suspicion of intraperitoneal bladder rupture should be kept in mind even though it has associated pelvic bone fracture in an adult patient.